Сombined Treatment of Juxtaand Parapapillary Choroidal Melanoma - V. V. Neroev; S. V. Saakyan; А. G. Amiryan; V. V. Valskiy; А. Iu. Tsygankov (Oftalʹmologiâ, 2020)
Purpose. Estimation the local efficacy of the combined treatment — brachytherapy (BT) with laser coagulation (LC) in choroidal melanomas of juxta and parapapillary localization in the long-term follow-up. Patients and Methods. In 2009–2013, 50 patients with choroidal melanoma of juxta and parapapillary localization were examined and treated, 32 women and 18 men aged from 32 to 76 years old (average — 53.8 ± 9.6 years). The averaged tumor height was 3.8 ± 1.3 mm, basal diameter — 11.2 ± 2.4 mm. The combined organ-preserving treatment included a LC from the optic disc with subsequent BT was performed. The indications for this method were choroidal melanomas of juxta and parapapillary localization (the distance between the optic disc and the central border of the tumor was no more than 1.5 pd), with the absence of subretinal exudate and retinal detachment in this zone. The follow-up period after the combined treatment ranged from 18 to 102 months (Me = 60 months). Results. Complete tumor resorption was achieved in the majority — 38 (76.0 %) of cases, partial — in 11 (22.0 %) patients, stabilization of the process — only in one (2.0 %) patient, continued growth was not observed in any patient. The initial size of melanoma in patients with complete and partial tumor resorption showed similar averaged values, amounting to 3.8 ± 1.3 mm and 3.6 ± 1.1 mm (p > 0.05), respectively, basal diameter — 11.1 ± 2.4 mm and 11.4 ± 2.4 mm (p > 0.05), respectively. According to the duplex scanning, an increase in the distribution density of bloodflow in the projection of the tumor focus was noted compared with the initial data. In the spectral Doppler flow analysis study, an increase in the linear characteristics of the blood flow in the tumor’s own vessels after LC was recorded. Complications included optic neuropathy (88 %), hemorrhage (36 %) and secondary glaucoma (6 %). Conclusions. The combined treatment allowed to achieve high therapeutic results — 76.0 % of the total resorption of choroidal melanomas, which have unfavorable localization for BT. Given the main focus of local treatment of the choroidal melanoma on its destruction, this technique can be used to increase the effectiveness of the BT of choroidal melanomas of juxta and parapapillary localization.